A moderate defense of cognitive phenomenology - Arıkan, Hakkı Kaan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
Is there a specific phenomenology of thinking? Cognitive phenomenology debate goes about possible answers for this question. According to a liberal conception of phenomenal consciousness, thinking has a sui generis phenomenology in addition to sensory phenomenology. A conservative conception of phenomenal consciousness rejects this liberal proposition and holds forth that the domain of phenomenology must be only sensory experiences. A detailed examination of the opposing arguments of the two rival approaches is the main topic of the present thesis study. The most common strategy for liberalism to argue for the existence of cognitive phenomenology is to appeal to introspection and claim that cognitive phenomenological properties are available to its subject by introspection. I propose that direct appeals to introspection cannot provide conclusive results and this is the main reason why conservatives cannot be persuaded by the liberal arguments from introspection. Another argument form that is commonly used by liberals is based on the notion of phenomenal contrast and liberals argue that the best explanation for phenomenal contrast scenarios is the existence of cognitive phenomenology. On the other hand, conservatives argue that the phenomenal contrast scenarios are explainable not by cognitive phenomenology but by sensory phenomenology and that there is no need to grant the existence of cognitive phenomenology. The general line of thinking of conservatives against the liberal arguments is a reductionist approach. I argue that this reductionist approach cannot prove the inexistence of cognitive phenomenology and support my claim with adverbialism. Moreover I argue that adverbialism conflicts with neither liberals nor conservatives and believe that the adverbialist approach can reconcile the two rival views.
Keywords: Phenomenology.; Cognitive psychology.